A survey of East Palaearctic Lycosidae (Araneae). 12. Two new Mongolicosa species from Mongolia - Fomichev, Alexander A.; Marusik, Yuri M. (Zootaxa, 2017)
Two new species of Mongolicosa Marusik, Azarkina et Koponen, 2004 are described from Mongolia: M. przhewalskii sp. n. (♀♂) and M. uncia sp. n. (♀♂). A map with distribution records of all known Mongolicosa species and descriptions of new species are provided.